Optimizing Regional Revenue: The Impact of Organizational Commitment on Performance with Citizenship Behavior as a Mediator - Ningsih, Luh Kartika; Kristinayani, Komang Dian; Yuliandari, Ni Kadek; Prastiwi, Ni Luh Putu Eka Yudi; Rauf, Ummu Ajrah Abdul (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the influence of organizational commitment, organizational citizenship behavior, and organizational performance. A quantitative research approach was used, as the study involves numerical data and statistical analysis. The population consists of all employees of the Bali Province Regional Tax and Retribution Services UPTD in Buleleng Regency. The sample of 90 respondents was selected using proportional random sampling. Primary data were collected through structured questionnaires measured on a Likert scale, while secondary data were obtained from books, journals, theses, and other relevant documents. The data were analyzed using Structural Equation Modeling (SEM), specifically the Partial Least Squares (PLS) approach, a variance-based SEM method. The findings reveal that: (1) organizational commitment has a positive and significant impact on organizational citizenship behavior, (2) organizational citizenship behavior positively and significantly affects organizational performance, (3) organizational commitment has a direct positive and significant influence on organizational performance, and (4) organizational commitment also indirectly influences organizational performance positively and significantly through organizational citizenship behavior. These results highlight the critical role of organizational commitment in enhancing both employee behavior and overall performance. Future research could explore additional factors influencing organizational performance, such as leadership style, job satisfaction, and workplace culture, to provide a more comprehensive understanding of organizational dynamics.